Spontaneous hemorrhage to the posterior cranial fossa, accompanied by occlusion-hydrocephalic syndrome - N. E. Polishchuk; O. N. Goncharuk; A. A. Oblyvach (Ukrainian Neurosurgical Journal, 2010)
From 150 patients with nontraumatic hemorrhages in posterior cranial fossa the occlusion hydrocephalic syndrome developed in 64, with expressive progression — in 36 patients. The diagnosis was established on the base of clinical data and additional methods — CT and MRI. 36 patients were operated because of progressive occlusion-hydrocephalic syndrome, 22 of them died (lethality 61%).